Educación y accesibilidad en museos: explorando el potencial de la comunicación transmedia (Ensayos) - Espinosa Barahona, Haidy (2025)
This essay addresses the confluence between education, accessibility and transmedia communication in museums, highlighting how digital transformations have facilitated the evolution of these institutions, from a unidirectional communication model to a more interactive and participatory one. Moreover, it addresses the accessibility barriers faced by historically excluded communities, such as the deaf community, proposing transmedia museography as a key tool to create inclusive environments to ensure access to knowledge. A three-stage model is propose that combines digital interactivity, in-person visits and the co-creation of content, promoting a more accessible and participatory museum model. The study concludes that transmedia communication transcends accessibility barriers by promoting dynamic, inclusive and participatory experiences under conditions of equality.